Impact of the Interventions in Coconut Based Homesteads as Perceived by Small Farm Families of Central Kerala - S. Helen and B. Shanmugasundaram, (Indian Journal of Extension Education, 2015)
An ICAR adhoc scheme on 'Possible Diversifications and Restructuring of Coconut based Homesteads' was implementedin the six agro-ecosystems of Central zone of Kerala covering three districts namely Palakkad, Thrissur and Ernakulamwith the holistic approach in coconut based homesteads with the participation of all the stakeholders. The impact of theinterventions as perceived by the participating farmers were assessed after three years of creating the preferredenterprises. When overall mean of positive effects in all the six agro-eco situations were assessed, it was found that the'Increased income' was realised as the highest positive effect with 4.97 mean score in the High Elevation Medium Rainfallsituation (HEMR-Kizhakkenchery). 'Discouraged because of slow growth of animals' was reported as the highestnegative impact with the mean score of 2.40 by the farmers of High Elevation-High Rainfall (HEHR) situation(Pananchery), that too showed 'lower' magnitude of negative effect. The interventions made under participatory modecreated 'higher' positive effects and 'lowest' negative effects in the small holdings of coconut based homesteads